Menelusuri Makna Kemanusiaan melalui Konsep Uti dan Frui Menurut Pemikiran Agustinus - Kevin Nobel Kurniawan (Reformed Center for Religion and Society, 2023)
Augustine of Hippo is a church father, and a major philosopher figure who influenced Christian thoughts in Western Europe. It is interesting to noted that Augustine had not only influenced the religious circle of Christianity, but he has also influenced various other fields. The works of Augustine can be depicted as a premodern form of existentialism. Neo-Platonism and Augustine’s original writings provide an explanation of the human experience and its mysterious pursuit of God, life’s meaning and ethics. This article attempts to explore the ethical thoughts of Augustine in regards of human ethics through the concepts of Uti and Frui. In the first section, this article provides the ground significance of Augustinian ethical thoughts and its relevance to criticise modern ethics. Second, a thorough background explanation of Neoplatonism and the concept of Uti and Frui will be provided to demonstrate human beings as ontologically different from other objects of things. Lastly, the author attempts to provide several critical thought of Augustinian thought and its relevance.